PEMBUATAN VIRGIN COCONUT OIL (VCO) DENGAN ENZIM PAPAIN - Diningsih, Ayus (Jurnal Kesehatan Ilmiah Aufa Royhan, 2021)
Virgin Coconut Oil (VCO) has a major role for the body, including reducing fat deposits in the body, reducing the formation of blood clots, controlling free radicals in cells, lowering blood and liver cholesterol levels, increasing antioxidant reserves in cells, and reducing the risk of heart disease and cancer. The purpose of this study was to determine the characteristics of the VCO produced by the papain enzyme. This research is a laboratory-based experimental research. The research was conducted at the Aufa Royhan University pharmaceutical chemistry laboratory in Padangsidimpuan City in November – December 2021. The main ingredient used is old coconut. The results showed that the VCO had a normal color and odor. The yield of the addition of 0% papain enzyme was 21.68%, 10% papain enzyme was 22.87%, 20% papain enzyme was 34.39%. Water content with the addition of 0% papain enzyme is 0.27%, 10% papain enzyme is 0.29%, 20% papain enzyme is 0.32%. The free fatty acid content with the addition of 0% papain enzyme was 2.93%, 10% papain enzyme was 3.04%, 20% papain enzyme was 3.706%. The conclusion of this study is that based on the yield of VCO, the more papain enzymes are used, the more VCO will be obtained. Meanwhile, the water content and free fatty acid content of the resulting VCO did not meet the SNI 2008 standard.